EVALUASI IMPLEMENTASI SISTEM E-LEARNING MENGGUNAKAN MODEL EVALUASI HOT FIT (STUDI KASUS UNIVERSITAS PAPUA) - Richard William Osok; Julius Panda Putra Naibaho; Alex De Kweldju (G-Tech: Jurnal Teknologi Terapan, 2025)
The advancement of information technology has significantly impacted education, particularly in the implementation of e-learning. Universitas Papua has adopted this system to enhance learning flexibility and efficiency. However, effectiveness depends on user adaptation and acceptance. This study evaluates the implementation of the e-learning system at UNIPA using the HOT-Fit evaluation model, which assesses Human, Organization, and Technology aspects. The research employs surveys and interviews with students and lecturers to measure user satisfaction, institutional support, and system quality. Findings indicate that technology, service, and information quality positively influence system usage and user satisfaction, ultimately contributing to system benefits. However, challenges remain, including infrastructure limitations and user adaptation issues that need improvement. This study provides valuable insights into the effectiveness of e-learning at UNIPA and offers recommendations for future system development. A comprehensive evaluation is essential to maximize benefits for students and institutions, ensuring accessible and high-quality education in the digital era.